(untitled) (ADMPG Journal, 2012)
People management is one area that has undergone more changes and transformations in recent years. The vision that we got to the area is totally different from its traditional situation, that received the name of Human Resource Management. This paper, as a result of academic research, the evaluation sought to establish that employees of a large company makes the action of the human resources area. The current stage of development of human resources shows that there is a signifi cant change over time.